السلوك العدواني لدى طفل الروضة وعلاقته ببعض المتغيرات "دراسة ميدانية لدى عينة من أطفال الرياض التابعة لريف دمشق" (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يعتبر العدوان سلوكاً طبيعياً وينبع من داخل الفرد, وينبغي عدم النظر إليه إلا على هذا الأساس ,واهتمت المجتمعات في العصر الحديث بمشكلات الصحة النفسية وكيفية الوقاية منها من جهة, والرعاية والعلاج من جهة أخرى.. وفي البحث الحالي كانت الأهداف تتمحور حول تشخيص مشكلة العدوان لدى طفل الروضة, ومن ثم التعرَف على الفروق في السلوك العدواني لدى طفل الروضة من حيث(العمر,الجنس..),أما مجتمع البحث فقد اشتمل على بعض الرياض التابعة لريف دمشق,والعينة تمثلت في "30 طفل وطفلة"ممن لديهم مشكلة العدوان,أما أداة البحث المستخدمة فكانت عبارة عن استمارة تقدير المعلمين للسلوك العدواني لدى طفل الروضة, وبعد عرض الباحثة لسلوك العدوان أسباباً ومظاهر وعلاجاً, وبسبب ندرة الدراسات التي تناولت هذا الجانب بالدراسة وخاصةً في مرحلة الطفولة المبكرة, توصلت إلى النتائج التالية بأن المستوى العلمي للأسرة كلما ارتفع كانت قدرة الوالدين على التعامل مع الأطفال العدوانيين أفضل وبالتالي يحصل الطفل على التربية السليمة,وبينت النتائج أيضاً أن الأطفال الذكور أكثر عدوانية من الأطفال الإناث, وبسبب هذا وُجب على الأسرة والروضة معاملة الأطفال الذكور والإناث بالأسلوب نفسه, ووجد البحث الحالي أن الأطفال كلما صغر عمرهم كان عدوانهم أكثر بسبب قلة قدرتهم على تنظيم سلوكاتهم , وهنا يأتي دور الروضة والأهل في مساعدة الطفل على التغلب على هذه المشكلة السلوكية والتخلص منها في مراحل حياته الأولى. Aggressive behavior is natural and comes from inside the individual and should only be viewed on this basis. Communities in the modern era are concerned with mental health problems and how to prevent them on one hand, and with care and treatment on the other. The objectives of this research focus on diagnosing the problem of aggression at kindergartens, and then identify the differences in aggressive behaviour at kindergartens in terms of (age, sex..). The research community has included some of the kindergartens of the suburbs of Damascus, with the sample consisting of 30 boys and girls experiencing the problem of aggression, The search tool used is an appraisal form for teachers to assess aggressive behavior at a given kindergarten. After introducing the phenomenon of aggression, that is,  causes, manifestations, and treatment, and because of the scarcity of studies on early childhood, we have drawn the following conclusion: the higher the parents' educational background, their ability to deal with children's aggressive behaviour gets better. Therefore, children get sound education, and the results also show that male children are more aggressive than their female counterparts; because of this, both parents and kindergartens should treat male and female children in the same way. The findings obtained show that children at an early age are more aggressive due to them lacking the ability to get their acts together, and here comes the role of kindergartens and parents in helping children overcome this behavioural problem and get rid of it at an early stage.